Feasibility and safety of hepatic artery infusion chemotherapy via the distal transradial access for hepatocellular carcinoma - Wu, Yi; Yu, Chunlin; Li, Xinghai; Zhong, Baoliang; Zeng, Daolin; Tian, Yunfei (Frontiers in Oncology, 2025)
Background and PurposeHepatocellular carcinoma (HCC) remains a global health challenge, with hepatic artery infusion chemotherapy (HAIC) serving as a pivotal treatment for unresectable cases. Traditional transfemoral access (TFA) for HAIC is associated with significant limitations, including prolonged immobility, increased risk of deep vein thrombosis (DVT), and reduced quality of life. The distal transradial access (dTRA), emerging as a viable alternative in coronary and neurovascular interventions, offers potential advantages in HAIC. This study evaluates the feasibility, safety, and clinical outcomes of dTRA for HAIC in HCC patients, addressing the paucity of data in this specific application.MethodsA retrospective analysis was conducted on patients who underwent dTRA-HAIC procedures for HCC between November 2023 and December 2024. The puncture time, procedural time, incidence of distal radial artery occlusion (d-RAO) and access site complications (ASC) were used to evaluate the treatment efficacy in the patients. Univariate and multivariate logistic regression analysis was performed to identify predictive factors associated with d-RAO development.ResultsThe mean puncture time was 3.5 minutes (3–4.25 minutes), with a distal radial artery diameter of 1.96 ± 0.16 mm. The mean catheter indwelling time for mFOLFOX-HAIC and Ralox-HAIC were 2375 minutes (1715–3276 minutes) and 410 minutes (276, 544 minutes), respectively. Early d-RAO rates were 25.4% on postoperative day 1, declining to 20.6% at 6 months. Multivariate analysis identified preoperative D-dimer levels (p < 0.05) as significant risk factors for early d-RAO in one-month after operation. Multiple punctures may be associated with a high risk of d-RAO. No severe bleeding, hematoma, or pseudoaneurysm occurred.ConclusiondTRA for HAIC demonstrates high technical feasibility and acceptable safety, representing a promising alternative to TFA. Preoperative D-dimer screening and limitations on repeated punctures may optimize outcomes. Larger multicenter studies are warranted to validate these findings and refine patient selection criteria.